Mass Diffusion Metamaterials with "Plug and Switch" Modules for Ion Cloaking, Concentrating, and Selection: Design and Experiments (Adv. Sci. 30/2022). Issue 30 (25th October 2022) - Li, Yang; Yu, Chengye; Liu, Chuanbao; Xu, Zhengjiao; Su, Yanjing; Qiao, Lijie; Zhou, Ji; Bai, Yang
Abstract : Modular Mass Diffusion Metamaterials A metamaterial design with reconfigurable functions realized by pluggable functional modules is proposed. In article number 2201032, Yang Bai and co‐workers demonstrate that ion cloak, ion concentrator, and ion selector can effectively manipulate the diffusion behaviors of ions in liquids solvents, which are expected to be widely used in applications such as catalytic enhancement and protein protection.